Daphne giraldii Nitsche (Thymelaeaceae): Phytochemistry, pharmacology and medicinal uses. (March 2020) - Han, Shuang; Li, Ling-zhi; Song, Shao-jiang
Abstract: Daphne giraldii Nitsche., a member of the genus Daphne (Thymelaeaceae), is a deciduous shrub with mild toxicity. Its rhizome bark, generally called 'Zushima' in Chinese, has many medicinal folkloric uses and good therapeutic effects. Previous studies investigating the chemical constituents and pharmacological activities of D. giraldii have focused on several major classes of compounds, such as coumarins, lignans and flavonoids, especially the interesting enantiomeric flavans. Extracts and pure compounds of D. giraldii were found to possess anti-inflammatory, anti-nociceptive, cytotoxicity, antimalarial, immunomodulating, sedative and hypnotic effects. They have also been reported to influence the cardiovascular functions and blood activities. This comprehensive review will describe the advances in the phytochemistry, pharmacology, medicinal uses and clinical applications of D. giraldii and its formulations covering the literature published from 1970 to 2018. Almost half of the reviewed studies were originally published in non-English languages (mainly in Chinese). Collectively, the aim of this article is to open new avenues for further in-depth pharmacological studies on D. giraldii. Graphical abstract: The medicinal uses, clinical application, phytochemistry and pharmacology of D. giraldii were reviewed. The main chemicals were coumarins and flavonoids with multiple prenyl substitutions. The structure-activity relationships (SAR) and mechanism of biological action were discussed. Image 1 Highlights: This review summarizes the phytochemistry, pharmacology, medicinal uses and clinical application of D. giraldii. The review expands the interest in the structure-activity relationships of flavones with multiple prenyl substitutions. Biological activities and mechanism of both isolates and individual compounds are gathered and analyzed.